Testing mediation roles of place attachment and tourist satisfaction on destination attractiveness and destination loyalty relationship using phantom approach - Muhamad Nasyat Muhamad Nasir (Management Science Letters, 2020)
The main objective of this research paper is to examine the mediating roles of place attachment and tourist satisfaction on destination attractiveness and loyalty relationship using the phantom approach among foreign tourists visiting Langkawi Island, Malaysia. Tourists from three countries listed in the top 20 international markets visiting Malaysia were chosen as the target population. The survey was conducted at the departure hall of Langkawi International Airport using a simple random sampling method. A total of 365 useful ques-tionnaires were returned and analyzed using Structural Equation Modelling (SEM). The findings of the study have empirically demonstrated that destination attractiveness had no significant direct influence on destination loyalty. However, the study discovered that tourist satisfaction and place attachment fully mediated the relationship between destination attractiveness and destination loyalty. Destination attractiveness has an indirect effect on destination loyalty. The study also illustrated that the tourist satisfaction factor had a stronger mediator effect than place attachment factor in the destination loyalty relationship model. The study suggested several insightful recommendations to the destination management office in maximizing tourist’s experience with cultural attractiveness and adequate infrastructure, thereby, enhancing the visitation of international tourists to Langkawi Island.